Photothermal detection of trace optical absorption in water by use of visible-light-emitting diodes - Hodgkinson, Jane; Johnson, Mark; Dakin, John P. (Optical Society of America, 1998)
Visible light emitting diodes of three different colors have been used to detect an absorbing compound (potassiumpermanganate) in trace quantities in aqueous solution. Photothermal absorption in a closed cell caused deflection of a water meniscus held at a small pinhole. The displacement was monitored using optical fiber interferometry. The technique was limited by LED emission intensities and environmental acoustic noise, giving minimum detectable absorption coefficients of 2x10-4 cm-1 at 478 nm and 658 nm, and 3x10-4 cm-1 at 524 nm. The magnitude and form of meniscus deflection signals were shown to be in good agreement with theory.